The Relevance of Islamic Education Concept Abdul Karim Amrullah's Perspective in the Contemporary Era - Wahyudi, Sahidin; Fatoni, Ahmad (Journal Corner of Education, Linguistics, and Literature, 2024)
The purpose of this study is to investigate the applicability of Abdul Karim Amrullah's conception of Islamic education in the modern day. Using a descriptive-qualitative methodology, this study examines a number of works that address the applicability of the idea of Islamic education from the viewpoint of Abdul Karim Amrullah in the modern period. The study's findings demonstrate that the curriculum or educational system put in place by Haji Rasul is still regarded as "ordinary" and masculine. According to multiple people the author spoke with, even Haji Rasul (HAMKA) "did not like" the curriculum and teaching strategies he employed at his Sumatra Thawalib school. At the local school where HAMKA first received his education, he thought he was having the most fun. He was quite constrained as a child, nevertheless, and did not feel as comfortable once his father moved him to Thawalib School in 1918. Therefore, rather than being overburdened with the stuff he had to memorize in class, tiny HAMKA decided to study in his own way, which involved spending more time in his teacher Zainuddin Labay el-Yunusy's library. But it is important to keep in mind that modern, more sophisticated education began with the Islamic education reform that Dr. H. Abdul Karim Amrullah, also known as Haji Rasul, initiated at the turn of the 20th century.